ANALYSIS OF THE EFFECTIVENESS OF RECEIVABLE MANAGEMENT AND CONTROL SYSTEMS AT CV AMA BERTIGA BANDUNG (Proceeding of SINERGY, 2026)
This study aims to analyze the effectiveness of receivables management and internal control systems at CV AMA Bertiga, located in Bandung City. The research is motivated by the relatively high level of outstanding trade receivables that have not been optimally collected, which may hinder cash turnover and the company’s financial stability. This study employs a qualitative descriptive approach, with data collected through interviews, observations, and documentation. The analysis examines receivables management practices supported by financial performance indicators, including Receivable Turnover (RTO), Average Collection Period (ACP), delinquency ratio, and collection ratio during the 2021–2025 period. The findings indicate that the effectiveness of receivables management at CV AMA Bertiga remains unstable. Fluctuations are observed in RTO and ACP, while the delinquency ratio tends to increase and the collection ratio shows a declining trend. These conditions suggest that the receivables control system has not been optimally implemented, particularly in credit policy, monitoring of receivables aging, and collection effectiveness. This study concludes that the company needs to strengthen its internal control system, tighten debtor selection, and improve collection mechanisms to minimize the risk of uncollectible receivables and maintain liquidity sustainability.